Applied Corporate Finance - Damodaran, Aswath (Hoboken, New Jersey : Wiley, 2015)
"Provides finance professionals with practical and succinct advice on how to do corporate finance rather than debate theory, assumptions, or models. Includes applications of corporate finance to real companies. Suitable for MBA program courses on corporate finance and equity valuation"--
(3SjO GdJhfSj (B/ (3cdjI GdGbJUGO hGdGOGQIs
Includes bibliographical references and index.
Keywords: Corporations -- Finance; BUSINESS & ECONOMICS / Corporate Finance